The 2017 regional elections in Slovakia: Soaring independents and recovered opposition in a fragmented political space. Issue 3 (27th May 2019) - Rybar, Marek
ABSTRACT: Government parties suffered defeat in the November 2017 regional elections in Slovakia. The Direction-Social Democracy (Smer), the senior coalition partner, managed to remain the party with the largest share of elected regional deputies. However, its strength was significantly reduced, both when compared to the 2016 national elections and the 2013 regional contests. The democratic center-right opposition managed to coordinate and compete effectively against the governing parties. Its success was apparent in the gubernatorial contests, where its candidates defeated most of the Smer-backed incumbents. The democratic opposition was less successful in elections to regional assemblies. Their most significant result is a dramatic increase in the share of independent deputies who constitute the largest virtual group of deputies.